Synthesis and properties of 2-(4-phenyl-5-(((5-phenylamino-1,3,4-thiadiazole-2-yl)thio)methyl)-1,2,4-triazole-3-yl)thio)ethanoic acid and its salts - A. S. Hotsulia; S. O. Fedotov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
Analysis of the literature over the past decade has shown that the chemistry of 1,2,4-triazole and 1,3,4-thiadiazole attracts considerable interest from scientists around the world because of the many valuable properties of compounds of this class. Bibliosemantic analysis shows that the nuclei of 1,2,4-triazole and 1,3,4-thiadiazole are fragments of a number of known drugs and biologically active compounds. That is why the synthesis and study of physical-chemical, biological properties of salts and acids containing these heterocyclic fragments are quite relevant both from a theoretical and practical point of view.